STUDI TENTANG PENINGKATAN TINGKAH LAKU SISWA MELALUI EKSTRAKURIKULER PRAMUKA - Khoirurido, Mohamad Fatkhul Huda; Rasidi, Rasidi (Universitas Muhammadiyah Magelang, 2013)
Purpose of this study was to determine the increase in student behavior through primary school extracurricular Candisari scout in Magelang District School. This research is a qualitative descriptive study. Research subjects are students who take extrascouts in SD Negeri Candisari Magelang regency. As for the object of his research is the behavior of the fourth grade students. Through extracurricular student behavior scout translated into 11 indicators and 25 items were measured using interviews, questionnaires, and field observations. The resulting data were then categorized and studied the theory to be true whether the conclusions drawn in accordance with the hypothesis or not. Hypothesis in this study is an increase in student behavior throughextracurricular scout. Data analysis techniques using qualitative descriptive analysis.This study has shown that an increase in student behavior through primary school extracurricular Candisari scout in Magelang regency. This can be proved from the research that students’ behavior can be increased from 68% to 91%. Increase positive student behavior through extracurricular scout also for their support, organization and development patterns in extracurricular scout in the school. So that students’ behavior will decrease if the absence or lack of extracurricular scout in SD Negeri Candisari Magelang regency.